The Leviathan expenses: Brief historical approach toward the evolution of the 19th – 21st Century Government budget - Saravia Salazar, Javier (2020)
The budget is one the most important management tools that the State has to its survival and that of its citizens. Its development and perfectionism go hand in hand with the political, economic, and social changes experienced by the State undergo. From a minimum state where the public expending is subordinate to the Executive Power willingness, we move to a public budget system that incorporate different political actors in the setting of public expending.  In the following lines we offer an approach to the public budget evolution, with special attention in the state transformation and the appearance of new political actors that intervene in the elaboration of its creation.